Strategy and Marketing Communication of Islamic Educational Institutions - Holilur Rahman; Samdani, Dani; Hasanuddin; Ahmad Budi Susanto (Penerbit Hellow Pustaka, 2024)
This article examines the concept of marketing strategies that can be applied by Islamic educational institutions. The purpose of the research is to identify and analyze effective marketing strategies in increasing the attractiveness and sustainability of Islamic educational institutions. The research method used is literature review and descriptive analysis based on marketing theories from experts such as Philip Kotler, Ali Hasan, and Fandy Tjiptono. The results showed that a good marketing strategy involves coordination of work teams, funding efficiency, and the right tactics to achieve goals. Basic marketing concepts such as production, product, sales, marketing, and social marketing need to be adjusted to the values, management vision, and market demands. In addition, effective communication patterns through publication of achievements, promotion, and advertising are also important in delivering marketing messages to the public. Good communication will influence public perception and increase trust in Islamic education institutions. In conclusion, the use of appropriate marketing strategies and effective communication can help Islamic educational institutions achieve their goals in meeting customer needs, gaining competitive advantage and strengthening relationships with the community.